Spiritualistic Humanistic Communication Strategy on Learning Aqidah Akhlaq at Madrasah Ibtidaiyah Negeri 1 Yogyakarta, Indonesia - Prastowo, Andi; Latief, Muhammad Jamroh (Nadwa: Jurnal Pendidikan Islam, 2019)
This study discusses the communication strategy in learning Aqidah Akhlaq to foster humanistic values and spiritualistic intelligence of learners in religious Elementary SchoolÂ  Madrasah Ibtidaiyah Negeri (MIN) 1 Yogyakarta. This study used a qualitative approach with case study method. Data were collected by in-depth interview, observation, and documentation, then analysed by interactive model. The results of this study revealed that communication strategy to cultivate the values of humanistic spirituality in MIN 1 Yogyakarta includes 3 three kinds: teachers as a compelling speaker, teachers as less effective preachers, and teachers as moderators.AbstrakPenelitian ini membahas strategi komunikasi dalam pembelajaran Aqidah Akhlaq untuk menumbuhkan nilai-nilai humanistik dan kecerdasan spiritualistik peserta didik di Sekolah Dasar Agama Madrasah Ibtidaiyah Negeri (MIN) 1 Yogyakarta. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan dengan wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis dengan model interaktif. Hasil penelitian ini mengungkapkan bahwa strategi komunikasi untuk menumbuhkan nilai-nilai spiritualitas humanistik di MIN 1 Yogyakarta meliputi 3 tiga jenis: guru sebagai pembicara yang meyakinkan, guru sebagai pengkhotbah yang kurang efektif, dan guru sebagai moderator.Â